Butylated hydroxytoluene induces astaxanthin and lipid production in Haematococcus pluvialis under high-light and nitrogen-deficiency conditions. (October 2018) - Zhao, Yongteng; Yue, Chenchen; Ding, Wei; Li, Tao; Xu, Jun-Wei; Zhao, Peng; Ma, Huixian; Yu, Xuya
Graphical abstract: Highlights: BHT induced astaxanthin and lipid production in H. pluvialis under abiotic stress. BHT alleviated the oxidative damage caused by abiotic stress. BHT upregulated the signal molecular level of nitric oxide. A useful strategy for lipid and astaxanthin synthesis was proposed. Abstract: The aim of this study was to investigate the effects of butylated hydroxytoluene (BHT) on the production of astaxanthin and lipids in Haematococcus pluvialis LUGU under high-light and nitrogen-deficiency conditions. Astaxanthin and lipid contents were increased by 71.13% and 10.71%, respectively, in algal cells treated with 2 mg L −1 BHT. The maximal contents of astaxanthin and lipids were 3.17% and 46%, respectively. The levels of reactive oxygen species (ROS) in the presence of BHT were lower than in the control, and this effect involved strong activation of several antioxidases. Additionally, BHT application upregulated endogenous nitric oxide (NO) production. These results showed that this approach is useful for stimulating production of astaxanthin and lipids in H. pluvialis and that exogenous BHT induces astaxanthin and lipid production, which is responsible for the signalling molecule responses against abiotic stress conditions in H. pluvialis .